Employment and Unemployment Rates of People Who Are Blind or Visually Impaired: Estimates from Multiple Sources. (November 2019) - McDonnall, Michele C.; Sui, Zhen
Introduction: We examined four sources of data to evaluate the employment status of people with visual impairments, including their current status and a comparison with previous years. Methods: Data from the American Community Survey (ACS) and three other nationally representative surveys were utilized to determine employment and unemployment rates for people with visual impairments and to determine whether employment rates have changed over time. Data from ACS were used to compare this population's employment and unemployment rates to people without disabilities and to people with other types of disabilities. Results: Unemployment rates for people with visual impairments ranged from a low of 4% (in 1994–1995) to a high of 19.8% (in 2011). Employment rates ranged from a low of 36.3% (in 2011) to a high of 44.2% (in 2017), based on ACS estimates. Estimates from all other data sources fall within this range. Based on ACS estimates, employment rates for people with visual impairments have not significantly increased over time. Large gaps in the employment and unemployment rates of people with visual impairments and those without disabilities exist, but these gap have significantly decreased over time. The smaller gaps in these rates for people with visual impairments and those with other disabilities have significantly increased over time. Discussion: These results indicate consistent employment rates for people with visual impairments across time and across different measurement methods and questions. The lowest employment rate, and highest unemployment rate, were recorded following the great recession, and these rates have been improving since 2012. Information for practitioners: Approximately 44% of the U.S. population with a visual impairment is employed, while 10% of people with a visual impairment (who are in the labor force) are unemployed. The remaining 50.9% of the U.S. population with visual impairments are not in the labor force.